The evolution of internationalization: towards a new theory? - Moreira,António Carrizo (2009)
The theories of internationalization encompass a wide variety of explanatory elements that follow the firms responses to distorted, imperfect markets. Whilst traditional theories were concentrated on foreign direct investment and on how multinationals enlarged their involvement in international markets, recent theories have focused their attention on small to medium businesses following either a staged model or a networked approach. There has been wide disagreement regarding all theories of internationalization. This paper provides a brief literature review on the main theories of internationalization and concludes that due to the emergence of a new polycentric economic world a new theory encompassing new important factors is in strong demand.